Determinan Profitabilitas, Ukuran Perusahaan, Dan Free Cash Flow Terhadap Kebijakan Dividen Yang Dimoderasi Oleh Likuiditas - Wicaksana, Dimas; Aris, Muhammad Abdul (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This research uses quantitative research. The purpose of this study was to determine whether liquidity can moderate the effect of profitability, firm size, and free cash flow on dividend policy. The sample of this study were 30 manufacturing companies listed on the Indonesia Stock Exchange in the consumer goods industry sector. The sample obtained from 2020-2022 amounted to 30 companies with. The data analysis method used in this study is the analytical tool used by researchers in the form of descriptive statistical analysis, classical assumption test, Multipe Regression Analysis (MRA) and hypothesis testing using SPSS version 26.0. The results provide evidence that company size affects dividend policy and liquidity can moderate liquidity on dividend policy, while profitability and free cash flow have no effect on dividend policy and liquidity fails to moderate profitability and free cash flow on dividend policy.